2020
DOI: 10.3389/fgene.2020.572414
|View full text |Cite
|
Sign up to set email alerts
|

SAP97 rs3915512 Polymorphism Affects the Neurocognition of Schizophrenic Patients: A Genetic Neuroimaging Study

Abstract: Our previous study suggested that the synapse-associated protein 97 (SAP97) gene rs3915512 polymorphism may influence neurocognition in schizophrenia patients. Neuroimaging studies have shown a possible association between cognitive function and brain activity/connectivity. Considering the poor understanding of whether the disease state and SAP97 rs3915512 polymorphism have interactive effects on brain activity/connectivity, 52 first-episode schizophrenia (FES) patients and 52 healthy controls were genotyped u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Taken together, these results are puzzling since it has been demonstrated a pivotal role of this synaptic element in regulating the trafficking of the glutamate AMPA receptors, whose expression, and function have been reported to be altered in SCZ [35]. In this regard, compelling evidence, including genetic-imaging studies, suggests that genetic variants of the DLG1 gene are functionally linked to abnormal cognitive patterns in SCZ patients [36][37][38][39][40]. In particular, Xu and colleagues reported that SAP97 rs3915512 polymorphism in patients with first-episode schizophrenia was associated with low structural and functional connectivity within the orbitofrontal-striatal-thalamic circuitry [41].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results are puzzling since it has been demonstrated a pivotal role of this synaptic element in regulating the trafficking of the glutamate AMPA receptors, whose expression, and function have been reported to be altered in SCZ [35]. In this regard, compelling evidence, including genetic-imaging studies, suggests that genetic variants of the DLG1 gene are functionally linked to abnormal cognitive patterns in SCZ patients [36][37][38][39][40]. In particular, Xu and colleagues reported that SAP97 rs3915512 polymorphism in patients with first-episode schizophrenia was associated with low structural and functional connectivity within the orbitofrontal-striatal-thalamic circuitry [41].…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA of all participants was extracted from EDTA-treated peripheral blood using the Tiangen DNA Isolation Kit (Tiangen Biotech, Beijing, China). As described before [ 17 ], the SAP97 rs3915512 polymorphism was examined using the improved multiplex ligation detection reaction (imLDR) technique (Genesky Biotech, Shanghai, China). The polymerase chain reaction (PCR) primers used for the rs3915512 polymorphism were as follows: rs3915512 forward primer: 5’-TGTTCAGGTGCATCAAGTGGTCTTTACA-3’, rs3915512 reverse primer: 5’-CTTCAGTAACTTCCAGTCAGATATGGCCT-3’.…”
Section: Methodsmentioning
confidence: 99%
“…Both the ANK2 and ANK3 genes show strong associations with SZ ( Luoni et al, 2016 ; Stevens and Rasband, 2021 ). Second, NrCAM is also associated with SAP97 ( Dirks et al, 2006 ), an adapter for glutamate receptors ( Waites et al, 2009 ; Li et al, 2011 ); SAP97 is associated with SZ, in particular with neurocognitive dysfunctions ( Uezato et al, 2017 ; Xu et al, 2018 , 2020 , 2021 ), and SZ-associated SAP97 mutations increase glutamatergic synapse strength in the dentate gyrus and impair contextual episodic memory ( Kay et al, 2022 ). Third, NrCAM is expressed in cortical astrocytes and neurons and forms perisynaptic contacts at inhibitory synapses.…”
Section: Introductionmentioning
confidence: 99%